Upaya Meningkatkan Kreativitas Siswa Dalam Pembelajaran Sejarah Dengan Pembuatan Storyboard Melalui Aplikasi Storyboardthat.com - Rahmi Rasyidah; Yani Kusmarni (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2020)
This study is entitled “Improving Student Creativity Through the Storyboardthat.com Application in Learning History (Classroom Action Research in Class XI C IIK MA EXACTLY 99 Rancabango). This research is motivated by the findings of researchers in Class XI C IIK MA EXACTLY 99 Rancabango which shows the low creativity of students in learning history. The creativity is very important to be developed and enhanced in learning one of them in learning history. Findings in class XI C IIK MA EXACTLY 99 Rancabago related to low creativity include low student curiosity, low student creativity in working on assignments and low student creativity in delivering information during presentations. This class action research was carried out in three cycles which in the first and second cycles were carried out three actions while in the third cycle two actions were carried out using the Dave Ebbut model. The purpose of this study is to increase student creativity in learning history. The creative aspects that are used as indicators in this study are based on Rachmawati and Kurniati’s opinions, including great or enthusiastic curiosity, having ideas and proposals, having different opinions from others, having high imagination and asking good questions and weighing. Obtaining a score from each indicator has increased in each cycle so that the acquisition of the score can be seen a result that shows an increase in creativity. Cycle I with a percentage of 62% increased by 12% in cycle II to 74% and increased again by 17% in cycle III to 91%. This shows the success of storyboarding through the application storyboardthat.com which is effectively applied in learning history to increase student creativity.